Structural changes and the differential expression of osteoprotegerin (OPG) and receptor activator of nuclear factor kb ligand (RANKL) in subchondral bone during the development of osteoarthritis - Akman, Akma Azmiera; Talib, Ain Aisyah; Md Yusof, Nur Azirah; Khalid, Kamarul Ariffin; Yusof, Nurul Asyiqin; Abdul Ghani, Radiah; Hamdan, Asmah Hanim; Zamli, Zaitunnatakhin (2018)
Osteoarthritis (OA) is a degenerative joint disease that is characterized by subchondral bone changes. Previous studies of OA have shown that structural changes were differed between subchondral bone plate (Sbp) and trabecular bone (Tb). However, the expression of OPG (bone formation) and RANKL (bone resorption) markers that underlying the differences between these two regions has yet to be determined. Hence, the present study aims to determine structural changes and expressions of OPG/RANKL in the Sbp and Tb during development of OA in Dunkin Hartley guinea pigs. Eighteen tibia was scanned using a micro-computed tomography (micro-CT) at three difference tome points; 10, 20 and 30 weeks of age to determine their Sbp and Tb thickness. Immunohistochemistry and histopathology methods were conducted to determine the expression of OPG/RANKL and microscopic OA score, respectively. The results showed that Sbp and Tb thickness were greater in the medial than the lateral side of tibial plateau, and increased significantly with ageing (p ≤ 0.01). In addition, across the time points, the OPG/RANKL ratio of medial Sbp was initially decreased, before being increased at the final time point. In contrast, the OPG/RANKL ratio of medial Tb was initially constant but then decreased at 30 weeks of age. Interestingly, a strong correlation was observed between the Sbp thickness and OPG/RANKL ratio with microscopic OA scores (r = 0.5, p ≤ 0.05), suggesting that the Sbp plays an important role in the pathogenesis of OA.